Extraction of Individual Spectra from Mixture Data Based on High-Resolution C-13-C-13 NMR Correlation Spectrum and DECODE Procedure - Cha, Jin Wook; Park, Sunghyouk (American Chemical Society, 2020)
In NMR analysis of complex organic molecules, low natural abundance of C-13 and the low resolution of two-dimensional (2D) experiments are significant difficulties. Also challenging is the analysis of a mixture spectrum without separation, which has been limited to simple molecules. Through nonuniform sampling using modified heteronuclear multiple bond correlation combined with indirect covariance, a high-resolution C-13-C-13 correlation spectrum was obtained with H-1 sensitivity. Built on the thus-obtained C-13-C-13 connectivities, deconvolution of the mixture spectra was achieved through a new signal-processing procedure, termed DECODE, tailored to the indirect covariance eigendecomposition. When applied to a complex natural product mixture of rotenone and brucine with many quaternary carbons, the method resolved very close carbon peaks and extracted clean individual spectra. Essentially providing molecule-wide C-13 connectivities for complex molecules from H-1-detected 2D spectra, our approach should prove useful in many areas of NMR analysis.